RESILIENSI 4.0 DAN DAYA SAING GLOBAL: STUDI INTERNASIONALISASI UMKM BERBASIS PRODUK LOKAL LAMPUNG - Rinaldi Bursan; Tiara Prisca Sabilla (Yayasan Nusantara Hasana Berdikari, 2025)
This study investigates the role of Resiliency 4.0 in enhancing the global competitiveness of small and medium enterprises (SMEs) in Lampung Province, Indonesia, focusing on local-based products such as coffee, processed fruits, and fisheries. Drawing upon the theoretical foundation of dynamic capabilities, organizational adaptation, and cyber-physical resilience, this research develops and tests a structural model linking Digital Capability (DC), Organizational Adaptation Capability (OAC), Cyber Resilience (CR), and Resiliency 4.0 (R40). Using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the findings demonstrate that DC and OAC significantly contribute to R40 both directly and indirectly through CR. Among the predictors, CR emerges as the strongest determinant, highlighting the pivotal role of digital asset protection, incident detection, and recovery planning in ensuring organizational resilience. The model explains 58% of the variance in R40 with acceptable predictive relevance, suggesting that Resiliency 4.0 offers a robust framework for SME survival and growth in the digital era. The study underscores the importance of integrating digital investment, adaptive culture, and cybersecurity readiness for SMEs in Lampung to achieve sustainable internationalization. Policy implications include strengthening digital infrastructure, promoting cybersecurity literacy, and fostering cooperative digital ecosystems.